Brain Histamine Modulates the Antidepressant-Like Effect of the 3-Iodothyroacetic Acid (TA1) - Laurino, Annunziatina; Landucci, Elisa; Cinci, Lorenzo; Gencarelli, Manuela; De Siena, Gaetano; Bellusci, Lorenza; Chiellini, Grazia; Raimondi, Laura (Frontiers in Cellular Neuroscience, 2019)
3-iodothyroacetic acid (TA1), an end metabolite of thyroid hormone, has been shown to induce behavioral effects in mice depending on brain histamine. We now aim to verify whether pharmacologically administered TA1 has brain bioavailability and it is able to induce histamine-dependent antidepressant-like behaviors. TA1 brain, liver and plasma levels were measured by LC/MS-MS in male CD1 mice, sacrificed 15 min after receiving a high TA1 dose (330 microgkg-1 ) The hypothalamic mTOR/AKT/GSK-beta cascade activation was evaluated in mice treated with 0.4, 1.32, 4 microgkg-1 TA1 by Western-blot. Mast cells were visualized by immuno-histochemistry in brain slices obtained from mice treated with 4 microgkg-1 TA1. Histamine release triggered by TA1 (20-1000 nM) was also evaluated in mouse peritoneal mast cells. After receiving TA1 (1.32, 4 or 11 µgkg-1; i.p.) CD1 male mice were subjected to the forced swim (FST) and the tail suspension tests (TST). Spontaneous locomotor and exploratory activities, motor incoordination, and anxiolytic or anxiogenic effects, were evaluated. Parallel behavioral tests were also carried out in mice that, prior to receiving TA1, were pre-treated with pyrilamine (10 mgkg-1; PYR) or zolantidine (5 mgkg-1; ZOL), or with p-cloro-phenylalanine (100 mgkg-1; PCPA). TA1 given i.p. to mice rapidly distributes in the brain, activates the hypothalamic mTOR/AKT and GSK-3 cascade and triggers mast cells degranulation. Furthermore, TA1 induces antidepressant effects and stimulates locomotion depending on the histaminergic system . TA1 antidepressant effect depends on brain histamine, thus highlithing a relationship between the immune system, brain inflammation and the thyroid